1997
DOI: 10.1002/(sici)1097-0142(19971001)80:7<1234::aid-cncr6>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Surgical pathologic factors that predict recurrence in stage IB and IIA cervical carcinoma patients with negative pelvic lymph nodes

Abstract: with pelvic lymph node dissection. The study group was composed of 196 lymph node negative patients. Pathology slides were reviewed and multivariate analysis 1 Department of Obstetrics and Gynecology, Acperformed to identify independent prognostic factors. ademic Medical Center, University of Amsterdam, Amsterdam, The Netherlands. RESULTS.The recurrence rate in the study group was 7.7%. In multivariate analysis, the following factors were identified as independent risk factors for recurrence: 2 Department of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 40 publications
1
22
0
2
Order By: Relevance
“…mit einer paraortalen Lymphonodektomie, unterzogen. Als entscheidende Prognosekriterien haben sich neben dem Alter der Patientinnen die histopathomorphologischen Kriterien Tumorgröße, zervikale Stromainvasionstiefe, Lymphknotenbefall, Lymphgefäßinvasion, Hämangiose sowie das Grading erwiesen [5,6,10,14,16,17,23,25].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…mit einer paraortalen Lymphonodektomie, unterzogen. Als entscheidende Prognosekriterien haben sich neben dem Alter der Patientinnen die histopathomorphologischen Kriterien Tumorgröße, zervikale Stromainvasionstiefe, Lymphknotenbefall, Lymphgefäßinvasion, Hämangiose sowie das Grading erwiesen [5,6,10,14,16,17,23,25].…”
Section: Introductionunclassified
“…mit einer paraortalen Lymphonodektomie, unterzogen. Als entscheidende Prognosekriterien haben sich neben dem Alter der Patientinnen die histopathomorphologischen Kriterien Tumorgröße, zervikale Stromainvasionstiefe, Lymphknotenbefall, Lymphgefäßinvasion, Hämangiose sowie das Grading erwiesen [5,6,10,14,16,17,23,25].Die Entscheidung zur adjuvanten Therapie beim operierten Zervixkarzinom wird zunehmend interdisziplinär in Abhängigkeit von diesen Risikofaktoren getroffen. Nach einer eigenen retrospektiven Analyse erhöht sich das relative Risiko, am Karzinomrezidiv zu sterben, beim operierten und nachbestrahlten Karzinom für das Stadium pT2b gegenüber pT1b nur um den Faktor 1,2, bei einer zusätzlichen Lymphknotenmetastasierung oder einer Lymphangiosis dagegen um den Faktor 1,7.…”
unclassified
“…Because patients with early cervical cancer have a favourable prognosis and adjuvant radiation treatment is associated with considerable acute or chronic adverse effects, identification of this high-risk group is crucial for physicians to avoid overtreatment (Sedlis et al , 1999; Peters et al , 2000; Ryu et al , 2011). Several clinicopathologic factors, such as tumour size, histology, lymphovascular space tumour involvement (LVSI), lymph node metastasis, and parametrial involvement, have been identified and analysed for prognostic significance (Delgado et al , 1989; Fuller et al , 1989; Samlal et al , 1997). …”
mentioning
confidence: 99%
“…According to the ‘Classic criteria', the intermediate-risk group includes patients with any two of the following three intermediate-risk factors: a) tumour size ⩾2 cm, b) LVSI, and c) stromal invasion of more than one-third of the cervical wall (Delgado et al , 1989; Samlal et al , 1997; Van de Putte et al , 2005; Ryu et al , 2011). Despite their simplicity and convenience, the Classic criteria provide low specificity and they are associated with a recurrence rate of 5–8% therefore, many researchers and physicians are reluctant to apply these criteria to sophisticated or toxic therapeutic agents in this patient group (Samlal et al , 1997; Ryu et al , 2011; Rogers et al , 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation